CNT work function modification for transparent electrode application in organic photovoltaics - Low, Keith Ying Jie. (2010)
As there is a need to develop higher power conversion efficiency and low cost photovoltaic (PV) cells, Organic PV (OPV) has sparked the interest of many to carry out more research work in this area. Currently Tin-doped indium oxide (ITO) is commonly used for one of the important components of OPV, i.e. the transparent conductive electrode. Because of ITO inflexibility, it limits its range of flexible application. Hence, Single walled carbon nanotubes (Cnt) are considered as a potential replacement because of its high conductivity and transparency properties but most importantly its flexible property. This project aims to alter the properties of Cnt to make it suitable for OPV applications. This project will focus on using various n- and p-dopants at various concentrations and doping timings to alter the work function and sheet resistance of the Cnt which are the key factors in OPV fabrication. The effects of the doping will be studied and analyzed. The results show that sheet resistance of the Cnt went down by more that 45% and there was in significant increase in the work function at concentration 4M of HNO3, a p- dopant. The n-dopant NADH also shows a 30% decrease in resistance and a fall in work function. The mechanisms of these changes will be discussed in more detail in the report. In conclusion, n- and p-doping can modify the work function and sheet resistance of the material but more future work has to be done to determine whether Cnt can be a viable substitute for ITO which will also be discussed in the report.